Impact of Iron Deficiency on Maternal Health During Pregnancy - Mohsen Al-Mosawei, Haneen Saeed; Al-Anbary, Saja H.F.; Khudhair Abbo, Hiba Muayad; Aljndeel, Hams Ahmed (Technium BioChemMed, 2025)
Iron requirements increase significantly during pregnancy to support fetal and placental growth, boost the mother’s blood volume, and compensate for delivery-related losses. A major public health concern, iron deficiency anemia (IDA) affects more than 20% of pregnant women in more than 80% of countries. Both the mother’s and the fetus’s health may suffer as a result, leading to fatigue and reduced productivity. Early laboratory screening, starting in the first trimester, is recommended to assess iron status. In this case-control study, serum ferritin and CBC data are collected from pregnant women with iron deficiency and healthy controls. Since many poor countries may not be able to provide an appropriate diet, early iron supplementation is essential. Education, prenuptial counseling, and prenatal care should raise public knowledge in order to promote a balanced diet and timely supplementation.